Turbulence in realistic geometries with moving boundaries: When simulations meet experiments. (15th January 2021) - Cappanera, L.; Debue, P.; Faller, H.; Kuzzay, D.; Saw, E-W.; Nore, C.; Guermond, J.-L.; Daviaud, F.; Wiertel-Gasquet, C.; Dubrulle, B.
Highlights: Bifurcation and Transition to Turbulence in Von Karman flow. entropy viscosity Large Eddy Simulation model. penalty method for moving solid obstacle in computational fluid dynamics. Comparisons numerical simulations and laboratory experiments. Abstract: Considering the current advances in experimental capabilities in fluid mechanics and the advances in computing power and numerical methods in computational fluid mechanics, a question that naturally arises is whether the two sets of techniques are approaching a level of sophistication sufficiently high to deliver results on turbulent flows in realistic geometries that are comparable. The purpose of this paper is to give elements of answers to this question by considering the so-called von Kármán flow where the fluid in a cylindrical container is driven by two counter-rotating impellers. We compare in the mentioned flow the torque and the flow topology obtained by experiments, direct numerical simulations (DNS), and large eddy simulations (LES) at various Reynolds numbers ranging from R e = O ( 10 2 ) to R e = O ( 10 5 ) . In addition to validating the proposed LES model, the level of agreement that is observed between the numerical and the experimental data shows that the degree of accuracy of each of these techniques is reaching a threshold beyond which it is possible to use each of them with high confidence to explore and better understand turbulence in complex flows at R e = O ( 10 5 ) and beyond.